Focal motor seizure in a wrestler with a sport-related concussion - Meehan, W. P.; Hoppa, E.; Capraro, A. J. (The Physician and Sportsmedicine, 2008)
Although sport-related concussion is a common injury, it is infrequently associated with seizure. While concussive convulsions, consisting of brief, generalized myoclonic activity while an athlete is unconscious have been described, the authors are aware of no published cases of concussion complicated by focal motor seizures. The authors describe the case of a 16-year-old male wrestler who sustained a sport-related concussion complicated by a focal motor seizure. The acute assessment and management of his injury, as well as follow-up until resolution of his symptoms, is presented. A brief review of the association between convulsive activity and mild traumatic brain injury follows.